2020
DOI: 10.24912/jmishumsen.v4i2.8849.2020
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Model Pengaruh Goal Orientation, General Self-Efficacy Dan Jenis Kelamin Terhadap Self-Regulated Learning Dalam Pembelajaran Jarak Jauh

Abstract: Since COVID-19's entry into Indonesia in early March, 2020, the government has determined all educational institutions to carry out learning activities using the Distance Education method. The method changes are so fast that students as students who use this method do not have much time to adjust and meet various obstacles. This study aims to see how self-efficacy and goal orientation influences students self-regulated learning while carrying out distance education. This study also wants to look at differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
1
1
0
5
Order By: Relevance
“…The adoption of GO performance, both approach and avoidance in this research sample, seems to be influenced by the learning situation at hand. In line with the results of preliminary studies from this research, the condition of PJJ, which is still a new thing for students, has an impact on reducing self-confidence in their ability to understand lecture material and having anxiety about the final results of their academic achievements (Neroni et al, 2018;Yudhistira et al, 2020). Self-confidence and GO are motivational variables that play an essential role in SRL and academic achievement (Honicke et al, 2020).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The adoption of GO performance, both approach and avoidance in this research sample, seems to be influenced by the learning situation at hand. In line with the results of preliminary studies from this research, the condition of PJJ, which is still a new thing for students, has an impact on reducing self-confidence in their ability to understand lecture material and having anxiety about the final results of their academic achievements (Neroni et al, 2018;Yudhistira et al, 2020). Self-confidence and GO are motivational variables that play an essential role in SRL and academic achievement (Honicke et al, 2020).…”
Section: Discussionsupporting
confidence: 70%
“…Various studies have found that students experience many challenges and obstacles during distance learning (Sadikin & Hamidah, 2020;Simanjuntak et al, 2020). A preliminary study conducted by researchers related to obstacles during lectures with PJJ to 144 students at one of the universities in Jakarta revealed several obstacles related to the learning process and technical obstacles such as learning devices and internet networks (Yudhistira et al, 2020). Some of the problems identified were unfavorable housing conditions, such as a crowded and noisy home environment.…”
Section: Introductionmentioning
confidence: 99%
“…Faktor motivasi memberikan pengaruh sebesar 0,6% -2,4% terhadap self-regulated learning (Chaerani, 2017); (Prastiwi, 2021) dan faktor orientasi tujuan memberikan sumbangsih sebesar 4,9% -24,9% terhadap self-regulated learning (Deasyanti, D., & Yudhistira, 2021); (Yudhistira, S., Deasyanti, D., & Muzdalifah, 2020) . Oleh karena itu, dapat disimpulkan bahwa faktor efikasi diri yang memberikan pengaruh lebih besar terhadap self-regulated learning bila dibandingkan dengan faktor lainnya.…”
Section: Pendahuluanunclassified
“…Penelitian yang dilakukan oleh Yudhistira, et al (2020) menunjukkan bahwa setidaknya terdapat 5 (lima) kendala yang dihadapi oleh mahasiswa selama melaksanakan Pembelajaran Jarak Jauh (PJJ), diantaranya ialah: 1) kendala Jaringan, 2) kendala Iklim rumah/tempat tinggal, 3) Penggunaan laptop atau peralatan lainnya yang berlebihan, 4) tugas yang lebih banyak dari biasanya, dan 5) menurunnya motivasi belajar dan terjadi kejenuhan. Hal ini menunjukkan bahwa terdapat banyak kendala baru yang dihadapi mahasiswa selama melaksanakan pendididkan dengan metode PJJ.…”
Section: Pendahuluanunclassified